Nafkah Isteri Ter-Thalaq Ba'in: Kajian Sejarah Sosial Pemikiran Imam Ahmad ibn Hambal - Rahman, Fuad (JURNAL AT-TURAS, 2017)
The obligation of ‘iddah for divorced women has been under rule of Islam. Meanwhile, it is also obligation for men to provide his divorced women a material support during ‘iddah period. It aims to facilitate her for living survival after the firstly time divorce. However, the rule possibly changes if the divorce is condemned in terms of thalaq ba’in, a condition in which the men takes three-divorce or state the third divorce to women with its implication to the prohibition for getting remarriage except only if the women has been under married by other men. For this case, the four ulama’s (with four schools of thought) have different decisions, but Imam Ahmad ibn Hambal determined that there is no obligation for providing material support for the divorced woman with thalaq ba’in. The enforcement of this law is based on the hadith as narrated by Asy-Sya’bi from Fathiman binti Qais from Rasulullah on the women with thalaq ba’in.